(untitled) (Revista Apotheke, 2023)
Is it possible to create other-becomings through the deformation of the subject’s image? By exploring the mixture between the languages of painting and photography, we investigated this possibility artistically through creations of deformations in transparencies. Here, the deformation is a disruptive pictorial power – a powerful means of suspending the subject in favor of becoming, based on the Logic of Sensation proposed by Gilles Deleuze in his book about the painter Francis Bacon. As a process, deformations are created in transparent acetate sheets and glass, experiencing its photographic developments through overlaps in different and multiple subjects. Photography is proposed here as poetry as it follows in the footsteps of Adolfo Montejo Navas, pushing the boundaries between reality and fiction, bringing art and life closer together as the artist Helena de Almeida did. Those crossings between different artistic languages and between subjects pursue the movement of becoming-other through the image. Philosophy and art are articulated in this search for thoughts and sensations that displace us from ourselves. It is a search with no end, as it is always in the transformation process.